Synthesis, characterization, and antibacterial activities of a heteroscorpionate derivative platinum complex against methicillin-resistant Staphylococcus aureus - Nam-Cha, Syong H.; Domínguez-Jurado, Elena; Tinoco-Valencia, Selena L.; Pérez-Tanoira, Ramón; Morata-Moreno, Noelia; Alfaro-Ruiza, Rocío; Lara-Sánchez, Agustín; Esteban, Jaime; Luján, Rafael; Alonso-Moreno, Carlos; Seguí, Pedro; Ocaña, Alberto; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Staphylococcus aureus is one of the species with the greatest clinical importance and greatest impact on public health. In fact, methicillin-resistant S. aureus (MRSA) is considered a pandemic pathogen, being essential to develop effective medicines and combat its rapid spread. This study aimed to foster the translation of clinical research outcomes based on metallodrugs into clinical practice for the treatment of MRSA. Bearing in mind the promising anti-Gram-positive effect of the heteroscorpionate ligand 1,1’-(2-(4-isopropylphenyl)ethane-1,1-diyl)bis(3,5-dimethyl-1H-pyrazole) (2P), we propose the coordination of this compound to platinum as a clinical strategy with the ultimate aim of overcoming resistance in the treatment of MRSA. Therefore, the novel metallodrug 2P-Pt were synthetized, fully characterized and its antibacterial effect against the planktonic and biofilm state of S. aureus evaluated. In this sense, three different strains of S. aureus were studied, one collection strain of S. aureus sensitive to methicillin and two clinical MRSA strains. To appraise the antibacterial activity, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), minimum biofilm inhibitory concentration (MBIC), and minimum biofilm eradication concentration (MBEC) were determined. Moreover, successful outcomes on the development of biofilm in a wound-like medium were obtained. The mechanism of action for 2P-Pt was proposed by measuring the MIC and MBC with EDTA (cation mediated mechanism) and DMSO (exogenous oxidative stress mechanism). Moreover, to shed light on the plausible antistaphylococcal mechanism of this novel platinum agent, additional experiments using transmission electron microscopy were carried out. 2P-Pt inhibited the growth and eradicated the three strains evaluated in the planktonic state. Another point worth stressing is the inhibition in the growth of MRSA biofilm even in a wounded medium. The results of this work support this novel agent as a promising therapeutic alternative for preventing infections caused by MRSA.